PMS (PREMENSTRUAL SYNDROME) PADA WANITA DAN PERUBAHAN EMOSI - TOGI FITRI A AMBARITA; PUTRI MARIATI; CINDY SIBURIAN; IIS WAWORUNTU (LP2MTBM MAKARIOZ, 2023)
Premenstrual syndrome (PMS) is a condition where a woman experiences hormonal changes that cause a biological reaction in the body which then causes changes in physical condition, emotions, and behavior; that occurs before menstruation until the completion of the menstrual phase. These changes will often interfere daily activities. The purpose of this study was to explain the relationship between PMS (premenstrual syndrome) and emotional changes in a woman. The method used is literature review through the Google engine. The author is looking for research results and scientific studies that explain the relationship between emotional conditions and premenstrual syndrome in women. Changes in the hormone estrogen, namely increasing serotonin levels which play a role in mood or emotion, are one of the mayor factor that cause PMS. Regulation of emotion plays important role in minimizing PMS syndrome. Risk factors that play an important role are stress and physical exercise.